Physiological stresses and adaptations to intensive training in children - Rowland, T. W. (1999)
There is growing evidence that children's aerobic response to endurance training is blunted in comparison with that of adults. Training studies in pre-pubertal subjects typically demonstrate a 5% increase in VO2 max, compared to a 15-30% rise in adults. Contrary to earlier ideas, pre-pubertal children have proved to be as capable as adults of improving muscle strength with resistance training. The extent that children can improve performance in short-burst, or anaerobic events, is not yet clear. Increases in anaerobic power have been reported in laboratory tests (such as the Wingate test), but such improvements have not always been seen in field events (i.e. sprint). A number of potential maladaptive affects of intensive athletic training in children have been suggested, but limited data are available to establish the validity of these concerns. Longitudinal echocardiographic studies of child athletes, as well as assessment of cardiac function after short races, have so far failed to reveal any adverse affect of training on a child's cardiovascular system. Animal studies have indicated that overstress of growing bones can stunt growth. However, cross-sectional and longitudinal studies indicate that size and rate of growth of children are not negatively influenced by intensive training and competition, which is of course very relevant to tennis. For child athletes, proper nutrition is critical, not only for good health and optimal sports performance, but also to satisfy the nutritional needs of the growth process. Limited reserach indicates, however, that these young athletes often sufer from important dietary deficits. The principal areas of concern involve inadequate total caloric intake, unbalanced diets and inadequate intake of iron and calcium. Child athletes differ from adults in their thermo-regulatory response to exercise. They sweat less, create more heat per body mass, and acclimatize more slowly to warm climates. Therefore, efforts need to be taken to protect young tennis players from over-exertion in hot, humid conditions.